Genggong In Tejakula Village | Genggong di Desa Adat Tejakula - Dwi Dharma Aditya; I Gede Yudarta (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
Genggong aimed to identify and concieve the appearance of form and function of Tejakula Genggong art. Nowadays, this art is still consistently performed but the interest of young generation of Tejakula Village to this art is decreased. where, there is only one group that is still consistent in preserving this Genggong art. The method that is used in this study is qualitative descriptive method, which purpose to describe the art of Genggong in Tejakula Village as it is referring to the research design. There are two theories which is used in this study, namely: (1) the first theory is the functions of music theory, in which the function can be realized when the art product has been achieved. This theory could preceded as an implication of ideas that is conceived in the minds of creators itself, and (2) second theory called aesthetic theory. This theory is divided into three derivatives knowledge that is accumulated in aspect of aesthetics, namely: ontology of art, epistemology of art, and social philosophy. The results of this study shown that the art of Genggong is the creation of Tejakula previous elders which the existence of it is still exist until today. This Genggong art is one of the vocal arts which the presentation is only used human voice using certain technique which is called ngongkek.